Authenticity, Risk and Co-Production: Immersive Digital Media in Decolonial Heritage Practice - Bouchard, Dominique (Mimesis Journal, 2024)
Between 2022 and 2024, English Heritage partnered with university and community colleagues to explore immersive XR technology alongside promenade theatre to interpret challenging narratives around enslavement and colonialism in the National Heritage Collection. The Mixed Reality project engaged a youth panel as paid consultants to help engage with, challenge and inform the project. Asking communities to help steer a project is sometimes considered a risk to authenticity, institutional expertise or research innovation. The article offers a risk framework in which community partnership is seen as a strategy for risk mitigation, aligning the aims of communities with heritage practitioners and researchers.